Integrating Presentation and Roleplay Activities in Teaching Business English Class in Boosting Students’ English-Speaking Fluency at Islamic Private University in Pontianak, Indonesia: Mengintegrasikan Aktivitas Presentasi dan Bermain Peran dalam Pengajaran Bahasa Inggris Bisnis untuk Meningkatkan Kefasihan Berbicara Mahasiswa di Universitas Islam Swasta di Pontianak - Marnangkok Pakpahan (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to describe the effectiveness of integrating presentation and roleplay activities in boosting undergraduate students’ English-speaking fluency in Business English class at tertiary level. The study is grounded in the problem that the awareness of English language instructors is often narrowly defined as declarative knowledge, without having sufficient attention to how such knowledge is enacted as procedural knowledge pedagogically. The study employs a qualitative case study design using observation and interview as the data collection method to assess data on the practice of declarative knowledge and procedural knowledge applied systematically. The findings reveal that presentation and roleplay activities significantly enhance students’ communication skills, particularly in terms of fluency, improved comprehension, contextual understanding, and interactive skills. Additionally, presentation and roleplay activities increase students’ confidence in speaking in English and encourage more frequent use of English in the classroom. Hence, the study results would benefit academicians in incorporating presentation and roleplay activities as effective tools in enhancing students’ communication skills in classroom activities. This study further elaborates on how presentation and roleplay activities, when used in a systematic and well-organized way, could optimize students’ participation in a Business English class, exploring more on their effectiveness in English communication skills, particularly English-speaking skills.